Optimization of Guidance and Counseling in Overcoming English Learning Problems for Madrasah Ibtidaiyah Students in Ternate City - Usman, Abdurrahman Hi.; Umar, Sitirahia Hi.; A. M. Arif, Nutfah; Adam, Adiyana (Electronic Journal of Education, Social Economics and Technology, 2025)
The purpose of this research is to examine the forms of guidance and counseling (BK) activities conducted at Madrasah Ibtidaiyah (MI) throughout the City of Ternate, as well as the optimization strategies implemented to help students overcome difficulties in learning English. This study uses a qualitative method with a descriptive approach, which allows the researcher to deeply describe the effectiveness of counseling and guidance services in supporting English language learning. The research results show that BK services are systematically integrated into English language learning through classical, individual, and group services. The optimization strategies implemented include preventive, curative, and developmental approaches, aimed at enhancing students' motivation, skills, and confidence in using English. The findings show that the optimization of guidance and counseling services has a positive impact on improving students' English language skills, as well as the development of adaptive and confident character. Although there are challenges such as the limited number of guidance counselors and low parental involvement, collaboration between guidance counselors and English subject teachers is key to improving service effectiveness. This research is expected to contribute to the development of guidance and counseling services at the elementary education level.